Interprofessional education with a community fall prevention event. - Sullivan, Karyn; Charrette, Ann; Massey, Colleen; Bartlett, Donna; Walker, Carrie; Bond, Irena; Bylaska-Davies, Paula; Scheidt, Natalie A.; Fong, Jeffrey J. (Journal of Interprofessional Care, 2015)
Implementation of interprofessional education (IPE) among multiple professional degree programs has many challenges. Students from four health science programs: pharmacy; nursing; physician assistant studies and physical therapy participated in an interprofessional community fall prevention event. This paper briefly describes the development of this IPE opportunity and the assessment of changes on students' attitudes about IPE after participation in the event. Differing views on teamwork and professional roles are reported by professions. Positive attitudes towards interprofessional teamwork were observed after participation in the event. Based on these data, it appears that an interprofessional community service event offers a useful approach forward for incorporating IPE into the curricula of different health care programs.